Epithelial-Cell-Derived Extracellular Vesicles in Pathophysiology of Epithelial Injury and Repair in Chronic Rhinosinusitis: Connecting Immunology in Research Lab to Biomarkers in Clinics - Toru Takahashi (MDPI AG, 2021)
Epithelial barrier disruption and failure of epithelial repair by aberrant epithelial-mesenchymal transition (EMT)-induced basal cells observed in nasal mucosa of chronic rhinosinusitis (CRS) are speculated to play important roles in disease pathophysiology. Microparticles (MPs) are a type of extracellular vesicle (EV) released by budding or shedding from the plasma membrane of activated or apoptotic cells. MPs are detected in nasal lavage fluids (NLFs) and are now receiving attention as potential biomarkers to evaluate the degree of activation of immune cells and injury of structural cells in nasal mucosa of subjects with sinus disease. There are three types of epithelial-cell-derived MPs, which are defined by the expression of different epithelial specific markers on their surface: EpCAM, E-cadherin, and integrin β6 (ITGB6). When these markers are on MPs that are also carrying canonical EMT/mesenchymal markers (Snail (SNAI1); Slug (SNAI2); alpha-smooth muscle actin (αSMA, ACTA2)) or pro- and anti-coagulant molecules (tissue factor (TF); tissue plasminogen activator (tPA); plasminogen activator inhibitor-1 (PAI-1)), they provide insight as to the roles of epithelial activation for EMT or regulation of coagulation in the underlying disease. In this review, we discuss the potential of epithelial MPs as research tools to evaluate status of nasal mucosae of CRS patients in the lab, as well as biomarkers for management and treatment of CRS in the clinic.